Exploring the Digital Frontier: Challenges and Opportunities in Sharia Banking Development - Hapiyah Hapiyah; Arum Marbawani; Yasara Nur Ramadhanty; Zaitun Qamariah (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This article is a literature review that discusses challenges and opportunities in the development of Sharia banking in the digital era. With the rapid development of technology, the Sharia banking industry is faced with various changes that affect operational methods, services, and interactions with customers. This study explores the various challenges faced by Sharia banking in the digital era, such as data security, technology integration, and regulatory adaptation. In addition, this article also discusses the opportunities that open up for the development of Sharia banking in the digital era, including the potential to increase financial access for the community, the development of innovative products and services, as well as the strengthening of relationships with customers through digital platforms. By understanding these challenges and opportunities, the Sharia banking industry can formulate the right strategy to take advantage of the potential of digitization in expanding coverage and improving sustainability.